Exfoliated Graphite Reinforced PMMA Composite: A Study on Nanoindentation and Scratch Behavior - Himel Chakraborty; Arijit Sinha; Nillohit Mukherjee; Partha Protim Chattopadhyay (Journal of Nanotechnology)
The present work aims to compare the scratch hardness (Hs) with the indentation hardness (HIT) obtained from nanoindentation measurements of exfoliated graphite/poly (methyl methacrylate) (EG/PMMA) composites. EG/PMMA composites with thickness 50 μm each were produced by in situ melt mixing method. Scratch hardness was measured from the scratch width formed at low applied load during the course of the scratch measurements. The measured scratch hardness values were compared with the indentation hardness. There is a good correlation between the scratch hardness and the indentation hardness at low indentation depths, with a linear relationship between hardness and the reinforcement content of exfoliated graphite.